COMMUNICATION COMPONENT IN THE FORMATION OF THE IMAGE OF HIGHER EDUCATION INSTITUTIONS BASED ON A MARKETING APPROACH - Буднікевич, Ірина Михайлівна; Бастраков, Данііл Анатолійович; Budnikevich, Iryna; Kolomytseva, Olena; Bastrakov, Daniil (My University, 2023)
The work examines the communication component in the formation of the image of higher education institutions. The variety of approaches to defining the "marketing of educational services" category is summarized. The marketing of higher education institutions is substantiated within the framework of various concepts of marketing in the conditions of competition: production concept, product concept, sales concept, classical concept, socio-ethical concept. Partnership concept of marketing is singled out as a philosophy of higher education institution functioning. Attention is focused on the need to develop and implement an active marketing policy and use modern marketing tools and technologies for the development of the ecosystem of higher education institutions. The necessity of forming the image of a higher education institution as a certain system of evaluations of various target audiences, which are formed due to effective marketing communications, is updated. Establishing a partnership and deepening cooperation with partners of higher education institutions using marketing tools is an important tool for image activities of higher education institutions. Emotional marketing is one of the elements of forming a positive image, bright emotions and a sense of belonging to higher education institutions. This component has a direct relationship with the marketing and advertising of the university, because disappointments from expectations damage the image and reputation of the brand. A communication policy or a promotion policy, which involves the unification of all communication channels, tools and means of conveying information about the educational brand, educational product and educational services to target audiences, is one of priority areas of marketing activities regarding image formation. The necessity of forming a communication strategy of a higher education institution consisting of marketing, creative and media strategies is substantiated. Social media as part of the global digital infrastructure, which includes social networks, professional platforms, blogs, wikis and many other formats, is singled out as an important communication tool of institutions. The advantages of social networks for universities, namely: improved communication, activation of the processes of recruiting and admission of students, connections with graduates, dissemination of knowledge, promotion of research and achievements, strengthening of the brand, image formation and management of the university's reputation have been identified.
Комунікаційна складова формування іміджу закладів вищої освіти на основі маркетингового підходу
Keywords: image activity of educational institutions; communication tools; image formation; partnership concept of marketing; marketing of educational services; emotional marketing